Agile development for urban digitalisation: insights from the creation of Dresden’s smart city strategy - Noennig, Jörg Rainer; Mello Rose, Filipe; Stadelhofer, Paul; Jannack, Anja; Kulashri, Swati (Measuring business excellence, 2024)
Purpose Digitalising cities requires new urban governance processes that account for rapidly changing environments and technological advances. In this context, agile development methods have become valuable, if not necessary. However, agile development contradicts public administration practices of risk aversion and long-term planning. The purpose of this study is to discuss practical avenues for navigating these two contradictions by adapting agile development to the needs of public sector organisations. Design/methodology/approach The authors review the collaborative elaboration of Dresden’s smart city strategy as a critical case study. Dresden’s smart city strategy was developed using agile development and quadruple-helix innovation. The year-long co-creation process involved stakeholders from various groups to conceive an integrated and sustainable vision for digitalisation-based urban development. Findings Despite the apparent contradictions, this study finds that key aspects of agile development are feasible for public sector innovation. Firstly, risks can be strategically managed and distributed among administration and non-administration stakeholders. Secondly, while delivering value through short iterative loops, adherence to formal processes remains possible. Informal feedback cycles can be harmoniously combined with official statements, allowing iterative progress. Research limitations/implications The empirical material is based on a single case study and thus risks overemphasising the general applicability of the proposed methods. Practical implications This paper outlines practical steps to greater agility for public administration engaged in digitalising cities. The paper conceptualises a forward and lateral momentum for the agile development of a smart city strategy that aims to reconcile formal policymaking processes with short-term loops and risk aversion with experimental value creation. This approach balanced risks, created value and enhanced the strategy‘s alignment with strategic frameworks, ultimately promoting innovation in the public sector. Originality/value This paper proposes a novel, empirically grounded conceptualisation of implementing agile methods that explicitly recognises the peculiarities of public administrations. It conceptualises the orchestrated and pragmatic use of specific agile development methods to advance the digitalisation of cities.